1999
DOI: 10.1159/000016554
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Wettability of Protein–Covered Hydroxyapatite Surfaces

Abstract: We developed a new method (dropping time method, DTM) to investigate the wettability of a surface of a protein layer adsorbed on glass plates in aqueous solution. However, the previous setup of DTM can only be utilized for optically transparent materials. In this study, we have extended the method to optically nontransparent materials such as hydroxyapatite plates. DTM is based on measuring the dropping time of a liquid film along a protein–covered surface when this surface is instantaneously vertically remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
1
10
0
3
Order By: Relevance
“…5,6 The amphoteric characteristics of titanium oxide that resulted from surface hydroxyl groups were reported to change its surface zeta potential as a result of the change in pH. 17,24,25 Surface analyses from our group using X-ray photoelectron spectroscopy indicated a 5.8 eV peak separation between the Ti 2p 1/2 and Ti 2p 3/2 peaks for the Ti surfaces and the TiO 2 single crystal standard. 26 In concurrence with other investigators, this peak separation and peak position indicated the presence of TiO 2 , with an oxidation state of 4ϩ.…”
Section: Discussionmentioning
confidence: 91%
“…5,6 The amphoteric characteristics of titanium oxide that resulted from surface hydroxyl groups were reported to change its surface zeta potential as a result of the change in pH. 17,24,25 Surface analyses from our group using X-ray photoelectron spectroscopy indicated a 5.8 eV peak separation between the Ti 2p 1/2 and Ti 2p 3/2 peaks for the Ti surfaces and the TiO 2 single crystal standard. 26 In concurrence with other investigators, this peak separation and peak position indicated the presence of TiO 2 , with an oxidation state of 4ϩ.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible that the mechanism of action is adsorption to the enamel and/or to the pellicle proteins. Certainly both casein and ovalbumin bind to hydroxyapatite: both contain phosphoserine sequences, which are known to be important in the binding of casein to hydroxyapatite [Reynolds et al, 1982;Kawasaki et al, 1999;Huq et al, 2000]. There is also evidence that related proteins can bind with salivary proteins; the casein-derived molecules caseinoglycomacropeptide and caseinophosphopeptide incorporate into the salivary pellicle as does whole casein.…”
Section: Discussionmentioning
confidence: 99%
“…apatite dissolution in simple acid solutions in vitro Hemingway et al, 2008], and this is thought to be due to adsorption of protein to the hydroxyapatite surface since both proteins are known to adsorb to hydroxyapatite [Reynolds and Wong, 1983;Kawasaki et al, 1999]. However, these studies used compressed hydroxyapatite as the dissolving substrate, instead of natural tissue.…”
mentioning
confidence: 99%
“…It has been also shown that the addition of food proteins (casein and ovalbumin) reduced enamel erosion [6], probably due to adsorption of protein to the hydroxyapatite surface [7]. The proteins might form a semi-permeable barrier, hindering transport of protons towards the hydroxyapatite crystal surface and/or calcium and phosphate ions away from the surface [8].…”
Section: Introductionmentioning
confidence: 99%